Resveratrol prevents EBV transformation and inhibits the outgrowth of EBV-immortalized human B cells. - J Luis Espinoza (Public Library of Science (PLoS), 2012)
Background Epstein Barr virus-associated lymphoproliferative disease is an increasing complication in patients with immunosuppressive conditions. Although the current therapies for this disorder are effective, they are also associated with significant toxicity. In an attempt to identify newer therapeutic agents, this study investigated the effects of Resveratrol, a naturally occurring polyphenolic compound, on the EBV transformation of human B cells. Methodology/principal findings This study demonstrates that resveratrol prevents EBV transformation in human B cells. These effects are mediated by specific cytotoxic activities of resveratrol against EBV-infected B cells that are associated with the downregulation of the anti-apoptotic proteins Mcl-1 and survivin. This occurs as a consequence of the inhibition of EBV-induced NFκB and STAT-3 signaling pathways and a resveratrol-induced decrease in the expression of the oncogenic viral product LMP1 in EBV-infected B cells. In addition, resveratrol decreased the expression of miR-155 and miR-34a in EBV-infected B cells, blocked the expression of the anti-apoptotic viral gene BHRF1, and thus interrupted events that are critical for EBV transformation and the survival of EBV-transformed cells. Conclusions/significance These results suggest that resveratrol may therefore be a potentially effective therapeutic alternative for preventing EBV-associated lymphoproliferative diseases in immune compromised patients.